Project Estimation Using the Use Case Points Method When Using Enterprise Architect - Wolski, Michał; Pilski, Marek (Studia Informatica. System and information technology, 2019)
This text is the third one from the series of articles concerning projects estimation in Enterprise Architect. In the first part ("Theoretical Aspects of Projects Estimation Using the Use Case Points Method" . White Paper published on Sparx Systems Enterprise Architect Community Site), theoretical aspects of the function points method have been presented. In the part two entitled: "Example of the Application of the Use Cases Points Method" (White Paper published on Sparx Systems Enterprise Architect Community Site) an example along with mathematical calculations have been discussed. Whereas in this part practical application of the function points method in Enterprise Architect have been presented.